The Effect of Brand Image and Product Quality on Scarlett Skincare Customer Loyalty at the Bussines Administration Science Study Program, Sam Ratulangi University Manado - Mumek, Firencia Maria (JURNAL ADMINISTRASI BISNIS, 2025)
This study aims to measure the effect of brand image and product quality on Scarlett skincare customer loyalty at the Bussines Administration Science Study Program, Sam Ratulangi University Manado. The method used is a quantitative approach, with a population of active students who have used Scarlett. The sample in this study amounted to 100 respondents, who were selected using purposive and snowball sampling methods based on certain criteria. The data analysis techniques used include validity test, reliability test, classical assumption test, multiple linear regression, t test, F test, and coefficient of determination (R²). The results showed that brand image partially had a positive and significant effect on customer loyalty, with a t-count value of 26.903 and a significance level of 0.000. In contrast, product quality has no significant effect partially on customer loyalty, with a t-count value of -0.704 and a significance of 0.483. Simultaneously, brand image and product quality have a significant effect on customer loyalty, as shown by the F test with an F-count value of 575.245 and a significance of 0.000. The coefficient of determination (R²) value of 0.922 indicates that 92.2% of the variation in customer loyalty can be explained by brand image and product quality.